Penentuan Pengaruh Jenis Pelarut Ekstraksi Terhadap Perolehan Kadar Senyawa Fenolat dan Daya Antioksidan Dari Herba Miniran (Phyllanthus niruri L.) - Zulharmitta Zulharmitta; Derisa Elrika; Harrizul Rivai (Jurnal Farmasi Higea, 2010)
The influence of solvents on the gaining of phenolic compounds and antioxidant activity of  meniran herbs (Phyllanthus niruri L.)  have been evaluated. The meniran herbs were extracted with  methanol-water, ethanol-water and acetone-water. Total phenolic content of these extracts were determined by using the Folin-Ciocalteau method and antioxidant activity of these extracts were determined by using  DPPH method. The results showed that extraction with methanol-water, ethanol-water and acetone-water give extractives in ammount of 167.9, 152.8 and 135.7 mg/g, respectively. The total phenolic compound content of these extracts were 73.4584, 59.9798 and 48.9976 mg/g respectively. Where as the antioxidant activity (IC50 value) of these extract were 0.3987,  0.4323 and 0.4495 mg/mL, respectively.